PENGARUH KONSENTRASI LARUTAN GARAM BERYODIUM (NACL) TERHADAP DAYA HAMBAT BAKTERI STREPTOCOCCUS MUTANS - Hermien Rimbiyastuti; Suwarsono Suwarsono; Ahmad Yusuf Julianto (Jurnal Kesehatan Gigi, 2016)
TITLEThe effect of iodized salt solution concentration against Streptococcus mutans growthABSTRACTIodium Salt solution is the combination of Na and Cl in water. The iodium salt could kill gram postitive and negative bacteria. Streptococcus mutans is one of bacteria that cause caries. The aim of this study wanted to know the effect of iodium salt solution in 20% and 80% concentration toward inhibitory ability of Streptococcus mutans.The type of this study was quasy experiment without control group. This study was the intervention of salt consentration toward inhibitory ability of bacteria.  The data were analyzed with quantitative descriptitive analyze.The result showed that the inhibitory effect of 20% salt solution was 5.3mm and 7.0mm for 80% salt solution. The cathegory inhibitory ability was moderate for 20% concentration and high for 80% concentration. The conclusion was that the 80% concentration of salt solution were more powerful in inhibitting Streptococcus mutans than 20%. Keywords : iodium salt solution, inhibitory ability, Streptococcus mutans